Analisa Pengaruh Variasi Rasio Katalis Zeolit Terhadap Pirolisis Limbah Kabel dan Limbah Ban - Zaenudin, Mohamad; Fadhlullah, Muhamad Vikri; Gamayel, Adhes; Priyadi, Muhammad Untung Zaenal (Nozzle : Journal Mechanical Engineering, 2024)
The accumulation of waste in the environment has become a critical issue, necessitating effective solutions, one of which is pyrolysis technology for treating waste such as tires and cables. Pyrolysis is a thermal degradation process that occurs under limited oxygen conditions, producing gas, tar, and char as byproducts. This study aims to evaluate the effect of varying zeolite catalyst ratios on the amount of oil produced and the production rate in the pyrolysis process of cable waste, tire waste, and their mixture. The catalyst ratios used in this study were 100, 200, and 300 grams, along with a control condition without a catalyst. The results indicated that the use of 300 grams of zeolite catalyst produced the highest oil yield, with 141 ml from cable waste, 233 ml from tire waste, and 238 ml from the mixed waste. In contrast, the absence of a catalyst yielded the lowest oil production, with 64 ml from cable waste, 85 ml from tire waste, and 137 ml from the mixed waste. These findings suggest that the use of zeolite catalyst significantly enhances both the production rate and quantity of oil compared to the condition without catalyst.